Tác động của kiến thức về trí tuệ nhân tạo tới hành vi đổi mới trong học tập thông qua dự án của sinh viên: Nghiên cứu tại Trường Đại học Ngoại thương - Bùi, Thảo Nguyên; Giáp, Thị Thoa; Nguyễn, Thị Hồng Anh; Hồ, Tùng Hiệp; Bùi, Thái Sơn (Tạp chí Giáo dục, 2025)
In the context of accelerating digital transformation in education in Vietnam, understanding and applying Artificial Intelligence (AI) has become an essential factor in innovating teaching and learning activities at the university level. However, there is still a lack of empirical studies on the relationship between AI literacy and students’ innovative behavior, an essential competency in the digital era. Therefore, this study was conducted at Foreign Trade University. The study reveals that students’ understanding of AI positively influences their innovative behavior. Specifically, students with foundational AI knowledge tend to proactively integrate tools such as chatbots, data analysis systems, and automation platforms into their projectbased learning. This not only enhances learning effectiveness but also fosters technological skills and the ability to solve real-world problems. The findings provide practical evidence for integrating AI-related knowledge into higher education curricula, particularly through project-based learning approaches.